Invasive Mechanical Ventilation and Mortality in Pediatric Hematopoietic Stem Cell Transplantation: A Multicenter Study*. Issue 4 (April 2016) - Rowan, Courtney M.; Gertz, Shira J.; McArthur, Jennifer; Fitzgerald, Julie C.; Nitu, Mara E.; Loomis, Ashley; Hsing, Deyin D.; Duncan, Christine N.; Mahadeo, Kris M.; Smith, Lincoln S.; Moffet, Jerelyn; Hall, Mark W.; et al.
Abstract : Objective: To establish the current respiratory practice patterns in pediatric hematopoietic stem cell transplant patients and investigate their associations with mortality across multiple centers. Design: Retrospective cohort between 2009 and 2014. Setting: Twelve children's hospitals in the United States. Patients: Two hundred twenty-two pediatric allogeneic hematopoietic stem cell transplant recipients with acute respiratory failure using invasive mechanical ventilation. Interventions: None. Measurements and Main Results: PICU mortality of our cohort was 60.4%. Mortality at 180 days post PICU discharge was 74%. Length of PICU stay prior to initiation of invasive mechanical ventilation was significantly lower in survivors, and the odds of mortality increased for longer length of PICU stay prior to intubation. A total of 91 patients (41%) received noninvasive ventilation at some point during their PICU stay prior to intubation. Noninvasive ventilation use preintubation was associated with increased mortality (odds ratio, 2.1; 95% CI, 1.2–3.6; p = 0.010). Patients ventilated longer than 15 days had higher odds of death (odds ratio, 2.4; 95% CI, 1.3–4.2; p = 0.004). Almost 40% of patients ( n = 85) were placed on high-frequency oscillatory ventilation with a mortality of 76.5% (odds ratio, 3.3; 95% CI, 1.7–6.5; p = 0.0004). Of the 20 patients who survived high-frequency oscillatory ventilation, 18 were placed on high-frequency oscillatory ventilation no later than the third day of invasive mechanical ventilation. In this subset of 85 patients, transition to high-frequency oscillatory ventilation within 2 days of the start of invasive mechanical ventilation resulted in a 76% decrease in the odds of death compared with those who transitioned to high-frequency oscillatory ventilation later in the invasive mechanical ventilation course. Conclusions: This study suggests that perhaps earlier more aggressive critical care interventions in the pediatric hematopoietic stem cell transplant patient with respiratory failure requiring invasive mechanical ventilation may offer an opportunity to improve outcomes.